BLENDED LEARNING: PEMANFAATAN TEKNOLOGI PADA PEMBELAJARAN BAHASA DI SEKOLAH - Yella Dezas Perdani (Merwinspy Publisher, 2023)
Blended learning is a pertinent topic in modern education due to the impact of globalization and technological advancements. Following the typology of blended learning practices, numerous institutions and professionals have formulated and characterized blended learning practices in their respective vocabularies. Amidst the Covid-19 pandemic, technology serves as a medium to connect lecturers and students who are unable to attend physical classes and engage in traditional teaching and learning methods. The utilization of technology in language learning is on the rise due to the advancements in language learning methods and techniques. Webinars are a crucial tool for disseminating knowledge among language educators and other professionals in the education sector. This community service (PKM) aims to provide teachers and education practitioners with the necessary skills to select appropriate teaching methods for their students and to prepare all the required resources for technology-based instruction. This training is anticipated to inform and prepare the teachers to use and implement the technology in the classroom, especially blended learning.